Encapsulation of a proteasome inhibitor with gold-polysaccharide nanocarriers - Sandra Rocha (2014)
Organic-inorganic hybrid nanoparticles are potential effective systems for drug delivery in cancer therapy and diagnosis. Chitosan-gum arabic with entrapped gold nanoparticles were developed as a carrier for an anticancer drug bortezomib. The nanosystem was designed to enhance the proteasome inhibitor activity in pancreatic cell lines, S2-013 and hTERT-HPNE. The hydrodynamic diameter of chitosan-gum arabic-gold nanoparticles loaded with bortezomib is around 330 nm. Laser scanning confocal microscopy images show the uptake of the gold nanoparticle/bortezomib encapsulated in chitosan-gum arabic matrix and the fast internalization of these nano combinations into pancreatic cells. Cytotoxic assays assessed that positively charged nanosystems reduce the cell growth and cell proliferation of S2-013s, but the same effect was not observed in cytotoxic response in hTERT-HPNE cells. The outcomes of this study demonstrate the capacity of chitosan-gum arabic nanocarriers to deliver gold nanoparticles/anticancer drug and to increase the permeation and retention effect in S2-013 cells and minimize drug side effects in HPNE cells. (c) 2014 Springer Science+Business Media.